Phenetic analysis of wing venation variability in Belarusian populations of the Altica oleracea (Linnaeus, 1758) (Coleoptera, Chrysomelidae, Galerucinae) - Nesterova, Oxana L.; Voronova, Nina V.; Dvornikova, Alexandra A. (Experimental Biology and Biotechnology, 2024)
A study of the leaf beetles A. oleracea venation polymorphism of the membranous wings from four Belarusian populations showed the presence of variability in the morphology of both main and secondary veins. All studied populations demonstrated the low level of intrapopulation diversity and the large proportion of rare morphs, most of which turned out to be unique for each population. A total of 28 wing venation phenes have been identified, of which 15 phenes are common to all populations, and 29 phenocomplexes, none of which are common to all populations. There was also no connection between the degree of fluctuating asymmetry of wing venation in populations and the ecological conditions of the environment in which the population lives.